Consequences of gas flux model choice on the interpretation of metabolic balance across 15 lakes. Issue 4 (1st January 2016) - Dugan, Hilary A.; Woolway, R. Iestyn; Santoso, Arianto B.; Corman, Jessica R.; Jaimes, Aline; Nodine, Emily R.; Patil, Vijay P.; Zwart, Jacob A.; Brentrup, Jennifer A.; Hetherington, Amy L.; Oliver, Samantha K.; Read, Jordan S.; et al.
Abstract: Ecosystem metabolism and the contribution of carbon dioxide from lakes to the atmosphere can be estimated from free-water gas measurements through the use of mass balance models, which rely on a gas transfer coefficient ( k ) to model gas exchange with the atmosphere. Theoretical and empirically based models of k range in complexity from wind-driven power functions to complex surface renewal models; however, model choice is rarely considered in most studies of lake metabolism. This study used high-frequency data from 15 lakes provided by the Global Lake Ecological Observatory Network (GLEON) to study how model choice of k influenced estimates of lake metabolism and gas exchange with the atmosphere. We tested 6 models of k on lakes chosen to span broad gradients in surface area and trophic states; a metabolism model was then fit to all 6 outputs of k data. We found that hourly values for k were substantially different between models and, at an annual scale, resulted in significantly different estimates of lake metabolism and gas exchange with the atmosphere.